2020
DOI: 10.3897/phytokeys.140.34574
|View full text |Cite
|
Sign up to set email alerts
|

Cryptocarya kaengkrachanensis, a new species of Lauraceae from Kaeng Krachan National Park, southwest Thailand

Abstract: A new species of Lauraceae, Cryptocarya kaengkrachanensis M.Z.Zhang, Yahara & Tagane, from Kaeng Krachan National Park, Phetchaburi Province, southwestern Thailand, is described and illustrated. This species is morphologically most similar to C. amygdalina in that its leaves are pinnately veined, leathery, and apparently glabrous (but microscopically hairy) abaxially, twigs are yellowish brown hairy, and fruits are 1.36 to 1.85 times longer than width. However, C. kaengkrachanensis is distinguished fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Other recent studies using MIG-seq on Hosta (Yahara et al 2021a) and Stellaria (Yahara et al 2021b) have also demonstrated its usefulness in resolving taxonomic complexity and describing new taxa. As this method is more applicable to a small number of poor-quality samples than RAD-seq (Binh et al 2018;Strijk et al 2020;Zhang et al 2020), it is expected to be used for taxonomic studies of many groups for which reliable phylogenetic relationships could not be reconstructed by conventional molecular phylogenetic methods. Japanese name.…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies using MIG-seq on Hosta (Yahara et al 2021a) and Stellaria (Yahara et al 2021b) have also demonstrated its usefulness in resolving taxonomic complexity and describing new taxa. As this method is more applicable to a small number of poor-quality samples than RAD-seq (Binh et al 2018;Strijk et al 2020;Zhang et al 2020), it is expected to be used for taxonomic studies of many groups for which reliable phylogenetic relationships could not be reconstructed by conventional molecular phylogenetic methods. Japanese name.…”
Section: Discussionmentioning
confidence: 99%
“…The method starts with multiplex polymerase chain reaction (PCR) using inter-simple sequence repeat (ISSR) primers; therefore, it is called multiplexed ISSR genotyping by sequencing (MIG-seq). Although they demonstrated its applicability for individual (clone) identification and population genetics analysis in their original study, recent studies have shown the efficacy of this method in molecular phylogenetic taxonomy in plants and animals Nguyen et al, 2020), including its application to museum specimens (Eguchi et al, 2020;Strijk et al, 2020) and for species identification and discovery in plants (Binh, Ngoc, Bon, et al, 2018;Okabe et al, 2021;Sakaguchi et al, 2020;Zhang et al, 2020) and corals (Richards et al, 2018;Takata et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Various molecular markers have been analyzed to develop plant DNA barcodes that can be readily sequenced and have a sufficiently high sequence divergence at the species-level [34,35]. These markers include the coding plastid regions, matK, rbcL, non-coding trnH-psbA intergenic spacer, and nuclear ribosomal internal transcribed spacer region (ITS) [36][37][38]. The DNA barcoding has been an essential tool for species identification and supplements traditional morphology-based taxonomy [33,39,40].…”
Section: Introductionmentioning
confidence: 99%